2002
DOI: 10.1038/sj.jim.7000226
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chromate by fixed films of sulfate-reducing bacteria using hydrogen as an electron source

Abstract: The ability of sulfate-reducing bacteria (SRB) to reduce chromate, Cr(VI), was evaluated using fixed-film growth systems and H2 as the electron source. A main objective of the experiment was to distinguish between direct enzymatic reduction and indirect reduction by hydrogen sulfide, in order to subsequently verify and control the synergy of these two mechanisms. In batch experiments with the sulfate-reducing consortium CH10 selected from a mining site, 50 mg l(-1) Cr(VI) was reduced in 15 min in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…In these previous experiments, it was shown that the chromium(VI) reduction capacity of the microbial biomass varied with the pH values of the culture medium, where the optimum pH values were found to be 7 in bacterial cultures (Schmieman et al, 1998;Ram et al, 1999;Nepple et al, 2000;Zouboulis et al, 2004). In the experiments with SRB, chromium(VI) reduction was also investigated at pH 7 (Tebo and Obratzsova, 1998;Smith and Gadd, 2000;Lloyd et al, 2001;Battaglia-Brunet et al, 2002). In the present study, the optimum value for chromium(VI) reduction at about 50 mg l À1 initial chromium(VI) concentration was found to be pH 8.…”
Section: Discussionmentioning
confidence: 97%
“…In these previous experiments, it was shown that the chromium(VI) reduction capacity of the microbial biomass varied with the pH values of the culture medium, where the optimum pH values were found to be 7 in bacterial cultures (Schmieman et al, 1998;Ram et al, 1999;Nepple et al, 2000;Zouboulis et al, 2004). In the experiments with SRB, chromium(VI) reduction was also investigated at pH 7 (Tebo and Obratzsova, 1998;Smith and Gadd, 2000;Lloyd et al, 2001;Battaglia-Brunet et al, 2002). In the present study, the optimum value for chromium(VI) reduction at about 50 mg l À1 initial chromium(VI) concentration was found to be pH 8.…”
Section: Discussionmentioning
confidence: 97%
“…It has been subsequently shown (Battaglia-Brunet et al 2002;2004a,b;2006) that this bioprocess was effective for removing chromate from different matrices (synthetic solutions, actual ground waters and actual waste waters), by using different supports (mainly pozzolana, ceramics and PVC crossfiller material), under continuous feed conditions, between 10 and 35°C, for several months, and in scaled up bioreactors (volume capacity of 2, 20 and 200 l). During the process development steps, whose main purpose was the efficient chromate immobilisation as Cr(III), certain aspects were not sufficiently detailed and we try to describe more precisely the process through some complementary experiments and investigations.…”
mentioning
confidence: 99%
“…Одним із основних шляхів появи резистентних до хромату мікроорганізмів може бути відновлення Cr (VI) до Cr (III). Відновлювати шестивалентний хром можуть мікроорганізми, що належать до родів: Acinetobacter [19], Aerococcus [51], Aeromonas [51], Aspergillus [23], Bacillus [57], Corynebacterium [55], Deinococcus [20], Desulfomicrobium [8,9], Desulfovibrio [13,33], Enterobacter [21,43,56], Escherichia [14,46], Microbacterium [38], Micrococcus [51], Ochrobactrum [19], Pseudomonas [10,11,32], Rhodobacter [36], Shewanella [35], Staphylococcus [44], Streptomyces [18], Vibrio [28] і Zoogloea [50]. Ефективно відновлюють Cr (VI) змішані культури сульфатвідновлювальних бактерій [48].…”
Section: вступunclassified